2007
DOI: 10.1016/j.amjhyper.2007.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Pressure Categories in Adolescence Predict Development of Hypertension in Accordance with the European Guidelines

Abstract: The risk of developing hypertension in young adulthood may be predicted by BP categories and BMI at adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 20 publications
2
20
1
4
Order By: Relevance
“…Adolescent rates of overweight/obesity in The Bahamas are definitely unacceptable as they mirror the high prevalence of overweight/obesity and a relatively high prevalence of EBP that exist in the adult population. This estimated prevalence of EBP was also consistent with other studies regionally [EBP of 14%], and globally ranging from 2.9%-24% (5,6,(12)(13)(14)(15)(16)(17)(18). The means for SBP and DBP in this study were lower than those found in Suriname and Tobago (5, 6).…”
Section: Discussioncontrasting
confidence: 34%
“…Adolescent rates of overweight/obesity in The Bahamas are definitely unacceptable as they mirror the high prevalence of overweight/obesity and a relatively high prevalence of EBP that exist in the adult population. This estimated prevalence of EBP was also consistent with other studies regionally [EBP of 14%], and globally ranging from 2.9%-24% (5,6,(12)(13)(14)(15)(16)(17)(18). The means for SBP and DBP in this study were lower than those found in Suriname and Tobago (5, 6).…”
Section: Discussioncontrasting
confidence: 34%
“…Generally, logistic regression was used to calculate the age-adjusted odds ratio for hypertension and the 95% confidence interval (CI). [21][22][23][24][26][27][28] Maffeis et al 29 performed a multivariate logistic regression analysis with backward stepping of variables and an evaluation of the model using three goodness of fit X 2 statistics, whereas Addo et al 13 used both univariate and multivariate regression models to calculate the odds ratio for hypertension. Barger and Muldoon 25 used the ordinal regression model, the cumulative odds model to evaluate differences in self-rated health as a function of hypertension status, labelling which further provides an extension of logistic regression for determining the odds ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is a high correlation between BP and growth of stature, weight and sexual maturity. 28,48,49 Voors et al 50 emphasize the need to define hypertension on several basal BP values as related to body weight and body dimensions rather than by age. Katz et al 51 reported that the variation of BP is closely related to growth and maturation in adolescents and children.…”
Section: Discussionmentioning
confidence: 99%
“…Megközelítően 970 millió hypertoniás ember él a világon, ebből a fejlett országokban 330 millió. 2025-re, alig több mint 10 év múlva, a becslések szerint mintegy 1,56 milliárd lakos lesz hypertoniás a világon [1,2,3,4].…”
Section: öSszefoglaló Közleményunclassified